Low Salinity Improves Photosynthetic Performance in Panicum antidotale Under Drought Stress - Hussain, Tabassum; Koyro, Hans-Werner; Zhang, Wensheng; Liu, Xiaotong; Gul, Bilquees; Liu, Xiaojing (Frontiers in Plant Science, 2020)
Salinity and drought are two often simultaneously occurring abiotic stresses that limit the production of food crops worldwide. This study aimed to distinguish between the separate and combined impacts of drought and salinity on the plant response. Panicum antidotale was cultivated in a green-house under the following growth conditions: control, 100 mM NaCl (100) and 300 mM NaCl (300) salinity, drought (D; 30% irrigation) and two combinations of salt and drought (100+D and 300+D). The growth response was as follows: 0≈100>100+D>>D≈300≈ 300+D. Growth correlated directly with photosynthesis. The net photosynthesis, stomatal conductance, intercellular CO2, transpiration, Rubisco, RuBP regeneration, triose-phosphate utilization protein (e.g. Phosphoenolpyruvate carboxylase) were highest in the control and declined most at 300+D, while 100+D performed significantly better as compared to drought. Maximum and actual PSII efficiencies along with photochemical quenching during light harvesting resemblance to the plant growth and contemporary CO2/H2O gas exchange parameters in the given treatments. Plant improves water use efficiency under salt and drought treatment that reflects the high water conservation ability of Panicum. Our findings indicate that the combination of low salinity with drought was able to minimize the deleterious effects of drought alone on growth, chlorophyll content, cell-integrity, photosynthesis, leaf water potential, and water deficit. This synergetic effect demonstrates the positive role of Na+ and Cl- in carbon assimilation and osmotic adjustment. In contrast, the combination of high salinity and drought enforced the negative response of plants in comparison to single stress demonstrating the antagonistic impact of water availability and ion toxicity.